VITAL PULPTHERAPY: MODERNTRENDS - Xudayberganova.M.X (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: To analyze modern trends and the evolution of materials used in vital pulp therapy. A review of clinical studies and meta-analyses conducted between 1960 and 2016 with a 12-month follow-up period was performed. The review highlights the shift from traditional materials like formocresol to bioactive materials such as Mineral Trioxide Aggregate (MTA) and Biodentine. MTA demonstrated superior biocompatibility and reparative properties compared to calcium hydroxide. Vital pulp therapy remains a biologically oriented and reliable approach, with modern biomaterials significantly improving clinical outcomes. Keywords: Vital pulp therapy, pulpotomy, mineral trioxide aggregate (MTA), formocresol, pulpitis, bioceramics, apexogenesis, primary teeth, dentistry, bioactive materials.